Exploring parental language ideology and language enrichment in Indonesian children’s translingual practices - Riski Aginia Hafizha; Sary Silvhiany; Soni Mirizon (UNIB Press, 2023)
There is an increased urgency of acquiring a lingua franca in this era of industrial revolution 4.0 and society 5.0 as language mastery plays a crucial role in meeting the 21st-century’s demand to compete globally. To this end, family literacy practices have become the keys for the family to socialize their children into the languages they think will benefit their children’s future. Despite the increasingly abundant research on bilingual/multilingualism, research on family English bilingual practice in Indonesian contexts is still limited. This paper is aimed to discuss family literacy practices and language enrichment used to acquire English in two Indonesian families in South Sumatra. A case study design was used to examine translingual practice. Interviews and observations were conducted to collect the data from the two families. Categorizing strategies (coding and thematic analysis) were accomplished to analyze the data. The findings of this study highlight translanguaging, code-switching, and code-mixing as the families’ common literacy practices at home. Another finding reveals the critical role of digital media, such as TV programs, YouTube videos, online games, and books, in supporting children’s English acquisition. Implications of this study include the need to pay attention to the family literacy practice as important component of understanding how second language socialization occurs outside of formal schooling and the role of digital media in mediating this socialization process.